2020
DOI: 10.1038/s41598-020-72853-3
|View full text |Cite
|
Sign up to set email alerts
|

Preoperative cardiac troponin below the 99th-percentile upper reference limit and 30-day mortality after noncardiac surgery

Abstract: Preoperative high-sensitivity cardiac troponin (hs-cTn) above the 99th-percentile upper reference limit (URL) is associated with mortality after noncardiac surgery. This study aimed to evaluate whether preoperative hs-cTn concentrations above the lowest limit of detection (LOD) but below the 99th-percentile URL can predict mortality after noncardiac surgery.From January 2010 to April 2019, a total of 12,415 noncardiac surgical patients with preoperative hs-cTn I below the 99th-percentile URL were enrolled. The… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
9
0

Year Published

2021
2021
2023
2023

Publication Types

Select...
8

Relationship

3
5

Authors

Journals

citations
Cited by 9 publications
(9 citation statements)
references
References 31 publications
0
9
0
Order By: Relevance
“…According to our result, preoperative cTn showed the largest effect on MINS, despite our inclusion of only patients with preoperative cTn level within normal range. In the perioperative period, cTn level even within the normal range was reported to be associated with outcome 17 . The current guidelines do not provide a clear recommendation for preoperative cTn measurement [2][3][4][5][6] , and only the guideline from Canadian society refers to the need for baseline cTn level 3 .…”
Section: Discussionmentioning
confidence: 99%
“…According to our result, preoperative cTn showed the largest effect on MINS, despite our inclusion of only patients with preoperative cTn level within normal range. In the perioperative period, cTn level even within the normal range was reported to be associated with outcome 17 . The current guidelines do not provide a clear recommendation for preoperative cTn measurement [2][3][4][5][6] , and only the guideline from Canadian society refers to the need for baseline cTn level 3 .…”
Section: Discussionmentioning
confidence: 99%
“…Two meta-analyses of 11 and 10 studies, published in 2016 and 2018, showed that PMI (indicated by troponins) was associated with major adverse cardiovascular events and mortality at 30 days and 1 year after non-cardiac, non-vascular surgery. 28 , 29 Still, the exact definition of PMI in relation to mortality should be investigated since Park et al 30 reported that patients with cTnI above the limit of detection but below the 99 th percentile had an increased mortality risk after non-cardiac surgery. Different cutoff points should be investigated in future studies.…”
Section: Discussionmentioning
confidence: 99%
“…[24][25][26] Additionally, high-sensitive cTn measurements at different time points 27 are encouraged to identify the potential prognostic role of tiny or subclinical acute myocardial injury (cTn concentrations between detection limit and URL) in patients with COVID-19 infection. [28][29][30][31] The major strength of this systematic review and meta-analysis is comprehensively exploring for the first time the potential linear or non-linear dose-response relationship between cTn concentrations and adverse clinical outcomes in COVID-19. Moreover, the study will focus on the significance of subclinical or tiny acute myocardial injury below the URL level for early diagnosis in order to improve prognosis and reduce related mortality.…”
Section: Discussionmentioning
confidence: 99%